2015
DOI: 10.1016/j.nbd.2015.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Selective reduction of striatal mature BDNF without induction of proBDNF in the zQ175 mouse model of Huntington's disease

Abstract: Huntington’s disease (HD) is a neurodegenerative disorder characterized by massive loss of medium spiny neurons in the striatum. However, the mechanisms by which mutant huntingtin leads to this selective neuronal death remain incompletely understood. Brain-derived neurotrophic factor (BDNF) has been shown to be neuroprotective on HD striatal neurons both in vitro and in vivo. ProBDNF, the precursor of mature BDNF (mBDNF), also can be secreted but promotes apoptosis of neurons expressing p75NTR and sortilin rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 61 publications
1
29
0
Order By: Relevance
“…We were unable to achieve specific labeling with the p75 antibody used in the Q111 and human post-mortem studies, and therefore a direct comparison with these studies is difficult (Brito et al, 2013, 2014). Interestingly, in the same Q175 model of HD used in this study, p75 levels were reported to be decreased at 12 months of age in both the heterozygous and homozygous mutants when compared to WT animals (Ma et al, 2015). p75 levels in the striatum, therefore, may vary depending on which HD mouse model is investigated.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…We were unable to achieve specific labeling with the p75 antibody used in the Q111 and human post-mortem studies, and therefore a direct comparison with these studies is difficult (Brito et al, 2013, 2014). Interestingly, in the same Q175 model of HD used in this study, p75 levels were reported to be decreased at 12 months of age in both the heterozygous and homozygous mutants when compared to WT animals (Ma et al, 2015). p75 levels in the striatum, therefore, may vary depending on which HD mouse model is investigated.…”
Section: Discussionmentioning
confidence: 57%
“…Some expression of p75 in MSNs has been reported previously (Brito et al, 2014). A recent study, however, indicates that the majority of p75 in the striatum is expressed in immature oligodendrocytes, suggesting at least some p75 signaling is non-cell autonomous (Ma et al, 2015). Additionally, this enhanced survival signaling may be through p75 alone, through p75/TrkB complexes, or through p75 complexed with a different receptor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NTs bind to two types of receptors, denominated tropomyosin receptor kinases (Trks) and 75‐kDa pan‐NT receptor (p75 NTR ), that are classically thought to regulate pro‐survival and death signaling, respectively. A majority of studies report that NTs and/or Trks levels decrease while p75 NTR content increases in HD brain . In accordance, preclinical studies employing small molecule ligands modulating both types of receptors succeed in preventing HD‐related pathology, improving cognition and motor abilities .…”
Section: Introductionmentioning
confidence: 75%
“…In addition, BDNF can promote functional recovery of injured neurons following spinal cord injury [12][13][14] and stimulate the production of new neurons in the adult brain 15,16 . Loss of BDNF has also been suggested as a contributory factor to the progression of PD [17][18][19] , AD 20 and Huntington's disease (HD) [21][22][23] , as well as conditions such as depression 24,25 .…”
Section: Introductionmentioning
confidence: 99%